Ansiedade, depressão e estresse, uso de álcool e outras drogas e a satisfação de discentes de pós-graduação stricto sensu - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá)
Postgraduate education is the meaning of many changes in the individual's life, which needs to adapt to new requirements that have never before been experienced, which becomes a challenge that affects their relationship with the academic environment, their family relationships and the well physical and psychic. The objective of this study was to identify levels of anxiety, depression and stress, level of satisfaction, perceived difficulties and the profile of alcohol and other drugs used by graduate students of the Federal University of Amapá. Method: The research was carried out in the descriptive type of quantitative character with transversal section. The study was carried out at the Federal University of Amapá in 11 postgraduate courses, with a sample of 139 students. For data collection, a socioeconomic and academic questionnaire was used along with the instruments Anxiety Depression and Stress-21 Scale to evaluate symptoms of anxiety, depression and stress, and the Alcohol, Smoking and Substance Involvement Screening Test to evaluate the risks of use of psychoactive substances. The quantitative data analysis was done through descriptive and inferential statistics with the Statistical Package for the Social Sciences program, and the qualitative data were analyzed through the technique of Collective Subject Discourse. Results: The majority of the population was aged between 20 and 30 years old, female, of brown ethnicity, with a family income above 5 minimum wages, in the state of Amapá, and as a source of income as a public servant. Among the subgroups of EADS-21 the one that presented the highest mean score was the stress that is classified as mild degree, then the symptoms of depression classified as moderate, third are the anxiety symptoms. Regarding the profile of use of psychoactive substances, the substance with the highest average in ASSIST were alcoholic beverages, followed by tobacco. The students had a space to justify the reasons for which they were satisfied or dissatisfied with the program, which originated the six speeches, among which four showed negative opinions and two with positive opinions. The reasons that led students to think about dropping out of the course are inherent to the project, extracurricular activities, relationship with the counselor and pressure with deadlines. Final Considerations: Educational institutions need to foster assistive and counseling policies that include postgraduate students, since this failure is perceived within the institutions, as well as working support groups to share experiences that lead to the approximation of students and teachers.
Keywords: Ansiedade; Depressão; Estresse; Abuso de substâncias psicoativas; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; EPIDEMIOLOGIA E SAÚDE PÚBLICA